Identification of TAPBPL as a novel negative regulator of T‐cell function. Issue 5 (3rd May 2021) - Lin, Yujun; Cui, Cheng; Su, Min; Silbart, Lawrence K; Liu, Haiyan; Zhao, Jin; He, Lang; Huang, Yuanmao; Xu, Dexin; Wei, Xiaodan; Du, Qian; Lai, Laijun
Abstract: T cell stimulatory and inhibitory molecules are critical for the regulation of immune responses. In this study, we identify a novel T cell co‐inhibitory molecule TAPBPL, whose amino acid sequence shares homology with known B7 family members. TAPBPL protein is expressed on resting and activated T cells, B cells, monocytes, and dendritic cells (DCs), as well as on some tumor tissues. The putative TAPBPL receptor is expressed on activated CD4 and CD8 T cells. A soluble recombinant human TAPBPL‐IgG Fc (hTAPBPL‐Ig) fusion protein inhibits the proliferation, activation, and cytokine production of both mouse and human T cells in vitro . In vivo administration of hTAPBPL‐Ig protein attenuates experimental autoimmune encephalomyelitis (EAE) in mice. Furthermore, an anti‐TAPBPL monoclonal antibody neutralizes the inhibitory activity of hTAPBPL‐Ig on T cells, enhances antitumor immunity, and inhibits tumor growth in animal models. Our results suggest that therapeutic intervention of the TAPBPL inhibitory pathway may represent a new strategy to modulate T cell‐mediated immunity for the treatment of cancer, infections, autoimmune diseases, and transplant rejection. Synopsis: T cells play a critical role in immune response. This study identifies a novel B7 family‐related T cell inhibitory molecule TAPBPL. Targeting the TAPBPL pathway may represent a new strategy to modulate T cell‐mediated immunity to treat autoimmune disease and cancer. TAPBPL shares sequence and structural similarities with existing B7 family members. TAPBPL protein is expressed on antigen‐presenting cells and cancer cells, whereas its receptor is expressed on activated CD4 and CD8 T cells. TAPBPL‐IgG Fc (TAPBPL‐Ig) fusion protein inhibits the proliferation, activation and cytokine production of T cells in vitro . Administration of TAPBPL‐Ig protein attenuates experimental autoimmune encephalomyelitis in mice. Anti‐TAPBPL antibody neutralizes the inhibitory activity of TAPBPL‐Ig on T cells, enhances antitumor immunity and inhibits tumor growth in vivo . Abstract : T cells play a critical role in immune response. This study identifies a novel B7 family‐related T cell inhibitory molecule TAPBPL. Targeting the TAPBPL pathway may represent a new strategy to modulate T cell‐mediated immunity to treat autoimmune disease and cancer.